Cathodic Corrosion Protection in the Context of Lifetime Extension of Monopile-based Offshore Wind Turbines - Stutzmann, Jutta (My University, 2017)
The first offshore wind farms face the end of their design lifetime in the upcoming years and with that service life extension becomes increasingly important. Offshore wind turbines are exposed to dynamic loads from wind and waves and to harsh environmental offshore conditions. Salt water and humidity abet corrosion on intermittently or completely submerged parts of an offshore support structure; free corrosion decreases the bearable loads. Hence, it is required to evaluate how long existing structures are effectively protected against corrosion. This thesis investigates a methodology to predict service life of cathodic corrosion protection systems applying on-site measurement data and simulations by means of the software COMSOL Multiphysics®. On-site measurement data of galvanic anode cathodic protection (GACP) systems and impressed current cathodic protection (ICCP) systems are provided from wind farms. Corrosion models for GACP systems are developed and calibrated to design and environmental data, like seawater and mud conductivity. Kinetic expressions, as simulation input, are iteratively fitted to measured potentials until simulation outcomes match existing potential data. Average current densities and protection potential at the monopile surface are calculated and compared to design and requirements. Sensitivity studies are applied to address model as well as measurement uncertainties, showing how important precises measurements are to allow on reliable lifetime predictions of cathodic protection systems. Results suggest that, e.g. anode capacity has a strong influence while other parameters have minor impact on the service life of GACP systems. Furthermore, this thesis indicates how predictions of cathodic protection performance can be applied to estimate on lifetime extension of the support structure of a monopile-based offshore wind turbine. The applicability of the approach is critically discussed, since results from simulation adjusted by measurements show high uncertainties. Nevertheless, an initial investigation to predict lifetime of corrosion protection systems is given. Improvement of potential measurements and specific environmental data would reduce uncertainties and allow for representative estimations on service life of corrosion protection systems.
Keywords: Energi; Materialvetenskap; Hållbar utveckling; Mekanisk energiteknik; Korrosionsteknik; Materialteknik; Energy; Materials Science; Sustainable Development; Mechanical energy engineering; Corrosion Engineering; Materials Engineering